China-Pakistan Economic Corridor (CPEC): A Threat to India’s Border Security - Sangkar, Manishahz A. P.; Mohd Huda, Mohd Ikbal (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">India has been averse to the Belt and Road Initiative (BRI) since its initial launch in 2013 because one of the core components of the initiative, the China-Pakistan Economic Corridor (CPEC), is perceived as violating the country’s sovereignty and territorial integrity. This article discusses the geostrategic execution of the China-Pakistan Economic Corridor (CPEC), which is viewed as a threat and constraint to India’s security. The article further analyses the perception of the Indian government towards the forged alliance between China and Pakistan. Along these lines, this disquisition explains the knowledge of how infrastructural techno-political regimes shape the threat towards Indian security. It does so by building on an analysis of India’s security strategy on China-Pakistan relations through the initiative of CPEC. The infrastructural techno-political regime of CPEC is discerned as a securitised threat by the Indian government. Infrastructure technology produced by CPEC promotes a securitised discourse of connectivity, flow, and territorial control as a cause of regional tension, national rivalries, unnecessary competitiveness, terrorism, and sovereignty issues. Simultaneously, other political entities might view the same regime as a border security threat.